Critical Analysis of the Relationship Between Qur’an Memorization and Learning Outcomes in Islamic Religious Education at the Elementary School Level - Nur Yahya; Imam Anas Hadi; Isnaini (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to critically examine the relationship between Qur’an memorization (tahfidz) and learning outcomes in Islamic Religious Education (PAI) at the elementary school level using a literature review approach. The research method employed is a systematic literature review, analyzing peer-reviewed journal articles, books, and relevant academic publications published between 2015 and 2025. The data were analyzed through a process of identification, classification, and synthesis to obtain comprehensive and valid conclusions. The results of the study indicate that Qur’an memorization has a positive and significant relationship with students’ learning outcomes in PAI. This relationship is reflected in three main domains: cognitive, affective, and psychomotor. In the cognitive domain, students involved in tahfidz activities tend to show improved memory capacity, concentration, and understanding of Islamic concepts. In the affective domain, memorization contributes to the development of discipline, learning motivation, and positive attitudes toward religious values. Meanwhile, in the psychomotor domain, students demonstrate better performance in Qur’anic recitation skills, including fluency and accuracy in tajwid. However, the effectiveness of Qur’an memorization in improving learning outcomes is influenced by several moderating factors, including teaching methods, teacher competence, learning environment, and student characteristics. Ineffective instructional design and excessive memorization load without adequate comprehension may reduce its educational impact. In conclusion, Qur’an memorization contributes positively to learning outcomes in Islamic Religious Education at the elementary school level, provided that it is implemented through structured, balanced, and student-centered learning approaches. This study recommends the integration of memorization and comprehension-based strategies to optimize students’ holistic development.